Good faith in the context of restitution of cultural property - Midorović, Sloboda D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The paper examines international and supranational rules on good faith in the context of restitution of cultural property. Deviations from the general rules on good faith with regard to the good faith acquisition and adverse possession have been indicated. Instead of insuring acquisition of property in conjunction with other preconditions, good faith only entitles an acquirer of the stolen or illegally exported cultural object to a fair compensation. The good faith presumption was abandoned and the burden of proof was imposed on the possessor of the cultural object. At the same time the criteria upon which the good faith should be evaluated had been tightened. Concerning gratuitous legal transactions, good faith of a transferee depends on good faith of a transferor. For that reason, a transferee will be prevented from claiming fair compensation if it would not have been awarded to his transferor. Ultimately, the paper explores in which legal sources and in what manner certain EU Member States have implemented good faith stipulations enshrined in Directive 2014/60/EU. Based on that, the paper suggests possibilities of harmonising law of the Republic of Serbia with the outlined supranational rules.